Evaluating shock index as a prognostic tool in septic shock patients - Laguvaram, Srikesh; G. M., Pranam; Hirevenkanagoudar, Usha; Chetty, Sanjeev (International Journal of Contemporary Pediatrics, 2025)
Background: Septic shock is a leading cause of morbidity and mortality in children worldwide. The shock index (SI), defined as a quotient obtained by dividing the heart rate (HR) with systolic blood pressure (SBP), is a potential tool that may aid in early prognostication of outcomes in paediatric septic shock, though data on its utility remains limited. Methods: A hospital-based cross-sectional study was conducted in the paediatric intensive care unit (PICU) at Navodaya Medical College, Raichur, over one year. A total of 100 children aged 1 month to 12 years with septic shock were included. SI values were calculated and analysed for their association with inotrope requirement, multiple organ dysfunction syndrome (MODS), length of PICU stay, and outcomes. Children with cardiogenic, hypovolemic, or obstructive shock and those previously treated at other centres were excluded. Results: Out of 100 children with septic shock, 76 survived and 24 died, with a mortality rate of 24%. Elevated SI values (>1.2) were seen in 78%, correlating with disease severity. Survivors had a mean SI of 0.9±0.1, while non-survivors had 1.3±0.2 (p<0.05). Among elevated SI cases, 64% required inotropes, and 42% developed MODS compared to 8% with normal SI (p<0.01). The average PICU stay was longer for elevated SI cases (7±3 days versus 4±1 days). Persistently high SI values predicted poor outcomes and mortality. Conclusions: Elevated SI can be a valuable non-invasive parameter that aids health care professionals in triaging sick children in a limited resource setting, allowing for timely referral to higher centres. Continuous monitoring of SI trends alongside HR and SBP can aid in early identification of high-risk patients, enabling timely and targeted interventions.